Acute Antihyperglycemic Activity of Kepok Banana Blossom (Musa paradisiaca L.) Extract in Mice - Rini Handayani; Rasidah; Munira; Noni Zakiah; Agus Hendra Al Rahmad (POLTEKKES KEMENKES PONTIANAK, 2026)
Banana inflorescence contains phytochemicals that may modulate postprandial glucose, but evidence for freshly prepared Kepok banana blossom is limited. This exploratory animal study evaluated the acute antihyperglycemic activity of 40%, 50%, and 60% fresh Kepok banana blossom (Musa paradisiaca L.) preparations using an oral glucose tolerance test. Twenty-five male mice were randomly allocated to distilled-water control, metformin control, or three extract groups (n = 5/group). Following fasting and oral glucose loading, blood glucose was measured before and after loading and at 30, 60, and 120 minutes after intervention. Qualitative screening detected alkaloids, saponins, flavonoids, phenolics, and tannins. At 120 minutes, mean glucose levels were 169.0 mg/dL in the negative control, 123.6 mg/dL with metformin, and 121.0, 136.6, and 125.0 mg/dL with the 40%, 50%, and 60% preparations, respectively. Descriptive mean-curve AUC values were 23,457, 18,525, 19,308, 19,650, and 19,740 mg/dL·min. These results suggest that fresh Kepok banana blossom preparations attenuated the acute glucose excursion compared with distilled water. However, the small sample, qualitative-only phytochemistry, nonstandardized dosing, and absence of a chronic diabetes model preclude conclusions about equivalence among concentrations, mechanism, or antidiabetic efficacy